2018
DOI: 10.1155/2018/3237253
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoxia-Mimetic Agent Cobalt Chloride Differently Affects Human Mesenchymal Stem Cells in Their Chondrogenic Potential

Abstract: Adult stem cells are a promising cell source for cartilage regeneration. They resided in a special microenvironment known as the stem-cell niche, characterized by the presence of low oxygen concentration. Cobalt chloride (CoCl2) imitates hypoxia in vitro by stabilizing hypoxia-inducible factor-alpha (HIF-1α), which is the master regulator in the cellular adaptive response to hypoxia. In this study, the influence of CoCl2 on the chondrogenic potential of human MSCs, isolated from dental pulp, umbilical cord, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…Severe and prolonged hypoxia may induce apoptosis, whereas acute and mild hypoxia induce adaptation and survival (Greijer and van der Wall 2004). Although previous studies have reported that dental-derived cells such as DPSCs and hPDLCs have high cell viability when cultured in 100 μM CoCl 2 (Osathanon et al 2015;Teti et al 2018), contradictory findings have also been reported, namely, that 100 μM CoCl 2 induced cell death (Laksana et al 2017). These conflicting results may be due to variations in cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Severe and prolonged hypoxia may induce apoptosis, whereas acute and mild hypoxia induce adaptation and survival (Greijer and van der Wall 2004). Although previous studies have reported that dental-derived cells such as DPSCs and hPDLCs have high cell viability when cultured in 100 μM CoCl 2 (Osathanon et al 2015;Teti et al 2018), contradictory findings have also been reported, namely, that 100 μM CoCl 2 induced cell death (Laksana et al 2017). These conflicting results may be due to variations in cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other hydroxylase inhibitors have also been used to create a physioxia mimicking response, specifically dimethyloxalylglycine (a competitive inhibitor of PHDs and FIHs) and desferrioxamine (sequesters iron ions). Although this review primarily focusses on experiments that use altered incubator oxygen levels, studies utilising chemically-induced physioxic responses are discussed where appropriate [36,39,40].…”
Section: Physioxia and Cartilagementioning
confidence: 99%
“…Currently, MSCs still represent a good candidate for tissue repair and regeneration [2,3]. MSCs or mesenchymal progenitor cells can be defined as non-hematopoietic, self-renewing cells that can be expanded ex vivo and induced to terminally differentiate, under certain conditions, into cells of mesenchymal lineage, including osteoblasts [4,5], chondrocytes [6,7,8], adipocytes [9], and hematopoietic-supporting stroma [10].…”
Section: Introductionmentioning
confidence: 99%